Cultural Attitudes and Technology - Heath, Jerome B. (Javnost-The Public, 1999)
This article uses several different instruments to survey students in Hawaii, representing both Asian and US origins. The results indicate that acceptance of technology correlates most directly with gender, father's education, and area of national/cultural origin, in contrast with measures of interest in media, acceptance of newness and new people, and concern about public issues. These results suggest that old conceptions concerning what drives the growth of technology are flawed, and that we must include attention to belief systems or mindscapes. Doing so leads us to adopt a cyclic epistemology, described by Maruyama and discussed as the dialectic by Hegel, as a better way of understanding how technology is appropriated in response to needs